Grobowce megalityczne na przedpolu Sudetów - Wojciechowski, Włodzimierz (Folia Praehistorica Posnaniensia, 2018)
A cemetery of megalithic long barrows of the so-called Kujavia type was discovered in autumn of 1995 near Muszkowice in the foothills of the Sudety Mountains. It consists of 6 trapezoidal structures made of stone and sand. It has been the first megalithic cemetery discovered in south-west Poland to date. Only one of the barrows (No. 2) has been partly excavated so far. Its dimension, use of stones as a building material and unchambered construction resemble similar structures known from Pomerania (the Łupawa type). The barrow has been dated back to the Funnel Beaker Culture.